O-007 Carotid stent cell design modified the periprocedural outcomes in the stenting arm of randomized trials of carotid revascularization: a meta-analysis. (4th July 2012) - Almekhlafi, M; Yavin, D; Mitha, A
Abstract : Introduction: Trials describe a risk of stroke of about 6% following carotid artery stenting (CAS). Stent cell design has been implicated as a potential factor in these risks. The small free cell area between the struts of a closed-cell stent theoretically provides better scaffolding of the vessel wall and superior plaque stabilization compared to the larger uncovered gaps in open-cell stents. No comparison between stent designs, and their relative effects on clinical outcome compared with carotid endarterectomy, has yet been published in the literature. Materials and Methods: This is an exploratory meta-analysis of randomized control trials (RCTs) comparing carotid endarterectomy (CEA) to CAS stratified by the stent cell design. A comprehensive literature search was conducted on major scholar search engines until July 2010. The primary outcome was a composite of the 30-day risk of stroke or death. A Mantel-Hansel random-effects model was used to calculate OR and 95% CIs. Results: Nine RCTs (4949 patients) were included in the final analysis. Closed-cell stent design was used in 807 patients and open-cell stents in 1657 patients, while 2485 patients were treated with CEA. The primary outcome was significantly lower in the CEA arm compared to CAS using open-cell design arm (OR 1.84, 95% CI 1.23 to 2.75; p=0.003). However, there was no significant difference in the primary outcome between CEA and CAS using closed-cell design, although a trend favoring CEA was noted (OR 1.54; 95% CI 0.69 to 3.47; p=0.29), Abstract O-007 figure 1 . If only the 30-day stroke rate was considered, the difference between CEA and CAS in the closed-cell stents is still non-significant (OR 2.92; 95% CI 0.52 to 16.21; p=0.22), compared to open-cell stents which continued to be inferior to CEA (OR 1.97; 95% CI 1.33 to 2.92; p=0.0007). Conclusion: In this meta-analysis of nine RCTs, CEA was not superior to CAS in trials using closed-cell stents. While these results may suggest better outcomes of CAS using the closed-cell stents, trials included in this analysis did not randomize patients to open- vs closed-cell stents. Furthermore, trials using the closed design recruited fewer patients than those using open-cell stents. Further assessment of a potential modification of CAS outcomes by stent design is underway with a meta-analysis of prospective CAS cohorts and registries to directly compare open- vs closed-cell stents. Competing interests: None.